Menyemai Asa di Pegunungan Meratus: Peningkatan Kapasitas Masyarakat dalam Pengelolaan Kopi di Desa Batu Perahu Kabupaten Hulu Sungai Tengah - Nabawi, Ahmad; Hamid, Ismar; Sari, Dini Puspita; Syahputri, Arya Vernanda; Salsabila, Putri; Dani, Muhammad Anwaruddin; Febrianty, Nur'Aulia; Bahjah, Noor; Roji, Fkah; Irfan, Muhammad; Hairida, Gusti (Prodi Sosiologi FISIP ULM, 2024)
Coffee is one of the commodities in Batu Perahu Village, Batang Alai Timur District, Hulu Sungai Tengah Regency, which is located on the slopes of the Meratus Mountains. One of the reasons for the low economic growth in society is that the potential of coffee has not been maximized. Therefore, the service team implemented the program